(untitled) (Bangladesh Journal of Public Administration, 2023)
Bangladesh is set to graduate from Least-Developed Country (LDC) status in 2026. After graduation from LDC status, Bangladesh will lose duty-free quota-free (DFQF) market access to export markets. Bangladesh’s export performance and robust economic growth record in recent times will be threatened due to the loss of preferential market access. The objective of this paper is to find the possible benefits, challenges and needed policy interventions for Bangladesh to sign and implement Free Trade Agreement (FTA) under Regional Trade Agreement (RTA) Policy 2022. A qualitative research design was applied for the study/evaluation. A mixed method of data collection has been followed where data from both primary and secondary sources have been collected. The study reveals that FTA results in preferential market access for exportable goods, attracting Foreign Direct Investment (FDI) and economic development. Lack of negotiation skills, possible revenue loss involved with FTA, resistance by industry groups, the unwillingness of counterparts to sign FTA with Bangladesh and geo-political sensitivity are major challenges at negotiation stage. Limited product basket, inadequate compliance and Non-Tariff Barriers (NTBs) are the major challenges at the implementation stage. Enhancement of negotiation skills, lower dependence on customs duty and generation of more revenues from other sources, political commitment, obtaining private sector support through inclusive approach, and proper coordination among agencies are found necessary for the successful negotiation of FTAs while diversification of export basket and facilitation of trade, and improved standards and certifications for compliance are vital to confronting implementation challenges.